Grouping of Nodes in Social Networks Based on Multiphase Approach - Boobalan, Parimala M. (Recent Patents on Computer Science, 2019)
Background: Recent advances in the field of information and social network has led to the problem of community detection that has got much attention among the researchers. Objective: This paper focus on community discovery, a fundamental task in network analysis by balancing both attribute and structural similarity. The attribute similarity is evaluated using the Jaccard coefficient and Structural similarity is achieved through modularity. Methods: The proposed algorithm is designed for identifying communities in social networks by fusing attribute and structural similarity. The algorithm retains the node which has high influence on the other nodes within the neighbourhood and subsequently groups the objects based on the similarity of the information among the nodes. The extensive analysis is performed on real world datasets like Facebook, DBLP, Twitter and Flickr with different sizes that demonstrates the effectiveness and efficiency of the proposed algorithm over the other algorithms. Results: The results depicts that the generated clusters have a good balance between the structural and attribute with high intracluster similarity and less intracluster similarity. The algorithm helps to achieve faster runtime for moderately-sized datasets and better runtime for large datasets with superior clustering quality.
Keywords: clusters